2014
DOI: 10.1371/journal.pone.0093289
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq-Based Analysis of Cold Shock Response in Thermoanaerobacter tengcongensis, a Bacterium Harboring a Single Cold Shock Protein Encoding Gene

Abstract: BackgroundAlthough cold shock responses and the roles of cold shock proteins in microorganisms containing multiple cold shock protein genes have been well characterized, related studies on bacteria possessing a single cold shock protein gene have not been reported. Thermoanaerobacter tengcongensis MB4, a thermophile harboring only one known cold shock protein gene (TtescpC), can survive from 50° to 80°C, but has poor natural competence under cold shock at 50°C. We therefore examined cold shock responses and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
0
17
0
1
Order By: Relevance
“…The upregulation of BCAA transporters at cooler temperatures was proved to transfer exogenous BCAA into cell for BCFA synthesis. Therefore, promoting BCFA portion could help to maintain the membrane fluidity of bacteria, which is a conventional strategy in cold adaptation [63]. The induction of BCAA transportation system in L .…”
Section: Resultsmentioning
confidence: 99%
“…The upregulation of BCAA transporters at cooler temperatures was proved to transfer exogenous BCAA into cell for BCFA synthesis. Therefore, promoting BCFA portion could help to maintain the membrane fluidity of bacteria, which is a conventional strategy in cold adaptation [63]. The induction of BCAA transportation system in L .…”
Section: Resultsmentioning
confidence: 99%
“…) and therefore was predicted to be able to sporulate in this and a previous study (Traag et al ). Although T. tengcongensis has not been observed to sporulate when it was first identified (Xue et al ), RNA‐seq has shown that a cold‐shock protein induces expression of sporulation genes in response to low temperatures (Liu et al ). We note that misclassification of SFF or NSFF will reduce the power to detect generation‐time effect.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, M. prima (grown at 35°C) contained branched, mono-unsaturated, and saturated fatty acids, while K. olearia (grown at 55°C) contained only saturated fatty acids (Nesbø et al 2012). Fatty acid composition is also part of the immediate coldshock response with genes involved in the production of, for instance, branched fatty acids being upregulated in the thermophile Thermoanaerobacter tengcongensis when grown at suboptimal temperatures (Liu et al 2014). Increase of branched fatty acids is a common response to lower temperatures (Suutari and Laakso 1994), and in Listeria monocytogenes this is due to temperaturedependent substrate selectivity of FabH, the enzyme responsible for the first condensation reaction in fatty acid biosynthesis (Singh et al 2009).…”
Section: Thermosipho Japonicus (Ab024932)mentioning
confidence: 99%